Il ruolo delle tecnologie del linguaggio nel monitoraggio dell’evoluzione delle abilità di scrittura: primi risultati - Alessia Barbagli; Felice Dell’Orletta; Giulia Venturi; Pietro Lucisano; Simonetta Montemagni (IJCoL)
Over the last ten years, the use of language technologies was successfully extended to the study of the language learning process. The paper reports the first promising results of an interdisciplinary study combining methods and analysis techniques from computational linguistics, linguistics and experimental pedagogy and aimed at tracking the development of written language competence over the years in high school students. In particular, the study is based on the computational analysis of essays written by Italian L1 learners, which were collected during the first and second year of lower secondary school, using automatic linguistic annotation and knowledge extraction tools. The analysis is carried out from a linguistic perspective, based on lexical, morpho-syntactic and syntactic features, by also taking into account students’ background information. Achieved results show that the distribution of features changes over time according to the development of student writing skills and led to the identification of a set of traits qualifying the learning process